The Influence of Tax Knowledge on Tax Compliance Behaviour: A Case of Yemeni Individual Taxpayers (Journal of Business Management and Accounting, 2020)
This paper aims to enhance the understanding of tax compliance behaviour of individual Yemeni taxpayers. It investigated the influence of tax knowledge on the behaviour of taxpayers. A survey was used to collect the required data. The major finding of this study is that tax knowledge of citizens has a significant influence on their likely compliance behaviour. Specifically, compliance behaviour increases when tax knowledge is higher. This study is probably among the first to investigate and to provide evidence on the influence of citizens tax knowledge on tax compliance behaviour in Yemen. The outputs of this study could serve as a useful input, not only for tax policy and strategy in Yemen, but also in other developing countries. Thus, governments are recommended to work on increasing tax knowledge of its citizens which will result in improving the level of tax compliance.